Co-evolution of horticultural breeding and product value chains: A product cycle perspective - Moniowska, Laura (International Food Policy Research Institute, 2024)
In an ever-evolving global market, the symbiotic development of new varieties of horticultural products in response to shifting international value chain priorities has become a pivotal factor in the expansion of the food industry. However, with rapid changes in product cycles and value chain processes, there are still significant gaps in how low and middle-income countries (LMICs) adapt and benefit from these innovations. Understanding these challenges, especially in the fruit sector, is crucial to unlocking the full potential of breeding and product development worldwide.